UPAYA PEMBATASAN KONSUMSI MAKANAN DAN MINUMAN MANIS MELALUI MEDIA EDUKASI: STUDI PADA ANAK SEKOLAH DASAR - Sari, Berliana; Gusfitriyani, Beti (Jurnal Informatika Medis, 2025)
The Theory of Planned Behavior (TPB) underlies an individual's intention to perform a specific behavior, including the behavior of restricting the consumption of sugary foods and drinks in children. This study aimed to evaluate the effectiveness of health promotion media based on TPB in limiting the intake of sugary foods and beverages among children aged 3–5 years. An experimental study with a pre- and post-test control group design was conducted, involving two groups with different educational media: the experimental group received messages through WhatsApp social media, while the control group received conventional leaflet-based education. The results showed that WhatsApp text messaging was effective in changing mothers' intentions, attitudes, subjective norms, and behaviors in restricting the consumption of sugary foods and drinks in children (p < 0.05). In conclusion, WhatsApp text messaging effectively influences mothers' intentions and behaviors in restricting sugary food and beverage intake in children, controlled by TPB constructs. WhatsApp-based educational media can be recommended as a health promotion strategy to prevent excessive sugar consumption in early childhood.